Translating biomass gasifier research to a market ready stove - Tillotson, James William, author; Marchese, Anthony, advisor; Clark, Maggie, committee member; Jathar, Shantanu, committee member (Colorado State University. Libraries, 2019)
To view the abstract, please see the full text of the document.
Keywords: combustion; emissions; TLUD; cookstoves; biomass; gasifier